PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN CORPORATE GOVERNANCE TERHADAP RETURN SAHAM - Bias Pungky Markuri, Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to examine empirical evidence the influence of profitability, leverage, liquidity, and corporate governance toward stock return on manufacturing companies listed in the Indonesian Stock Exchange in the period of 2016-2018. The sample in this research was determined by purposive sampling method. The research conducted by taking 37 manufacturing companies. The result of this research shows that leverage, liquidity and corporate governance have no significant effect on stock return. Profitability has significant positive effect on stock return.